Analyzing The Approach And Role Of The Gendarmerie Force Towards The Two Events Of The First World War And The Third Coup Of March 1299/1920 - Hashem Aghajari; saeed Agharezaee (مجله مطالعات ایرانی, 2023)
AbstractThe establishment of a national military force was one of the first plans of the nation's representatives in the first constitutional parliment. The short life of the parliament and Mohammad Ali Shah's coup became one of the main obstacles in realizing this goal. With the efforts of representatives and libertarians in the second parliament, the governmental gendarmerie force was established. A force that played a dynamic and active role in the country's developments from the time of its formation until its integration into the unified army. This essay tries to research the influence of the gendarmerie forces in the two events of the First World War and the coup on third of Esfsnd 1299 (february 22nd 1920) by analyzing the bases. The essay examines the issue through a historical method with a descriptive-analytical approach and the findings of the research show that the connection of a group of gendarmerie officers with the democrats and the independence of Iranian officers led to the union of the gendarmerie with the nationalists in opposition to the forces of Tsarist Russia and England; But the damage of the war and the deep financial and political crises that had led the country to the abyss of disintegration and subjugation, took the ideals and goals of the gendarmerie officers and the gendarmerie force reacted to this situation with passivity and the cooperation of a part of this force with the coup  on third of Esfsnd 1299 (february 22nd 1920)accompanied.